Proceedings of the 37th International ACM SIGIR Conference on Research &Amp; Development in Information Retrieval 2014
DOI: 10.1145/2600428.2609457
|View full text |Cite
|
Sign up to set email alerts
|

Rendering expressions to improve accuracy of relevance assessment for math search

Abstract: Finding ways to help users assess relevance when they search using math expressions is critical for making Mathematical Information Retrieval (MIR) systems easier to use. We designed a study where participants completed search tasks involving mathematical expressions using two different summary styles, and measured response time and relevance assessment accuracy. The control summary style used Google's regular hit formatting where expressions are presented as text (e.g. in L A T E X), while the second summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…how search hits are presented to the user [36]. In a recent study it was confirmed that as one expects, the formatting of math expressions significantly affects relevance assessment of search hits [25]. The normal hit format provided by Google (e.g.…”
Section: Introduction: Why Math Search Pertains To the Massesmentioning
confidence: 86%
“…how search hits are presented to the user [36]. In a recent study it was confirmed that as one expects, the formatting of math expressions significantly affects relevance assessment of search hits [25]. The normal hit format provided by Google (e.g.…”
Section: Introduction: Why Math Search Pertains To the Massesmentioning
confidence: 86%